2020
DOI: 10.1152/japplphysiol.00097.2020
|View full text |Cite
|
Sign up to set email alerts
|

The proteomic response is linked to regional lung volumes in ventilator-induced lung injury

Abstract: It is unclear how acid induced lung injury alters the regional lung volume response to mechanical ventilation (MV) and how this impacts protein expression. Using a mouse model, we investigated the separate and combined effects of acid aspiration and MV on regional lung volumes and how these were associated with the proteome. Adult BALB/c mice were divided into four groups: intratracheal saline, intratracheal acid, Saline/MV or Acid/MV. Specific tidal volume (sVt) and specific end-expiratory volume (sEEV) were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…In a rat ARDS model, overexpression of PRDX1 increased the release of IL-6, IL-8, and TNF-α [ 166 ]. Yen et al [ 167 ] showed that, in a rat model, tidal volume was associated with the expression of complement/coagulation cascade proteins, and low end-expiratory lung volumes were associated with expression of mitochondrial respiratory chain protein. They concluded that that tidal stretch and lung collapse can activate different pathways.…”
Section: Omics In Ards Researchmentioning
confidence: 99%
“…In a rat ARDS model, overexpression of PRDX1 increased the release of IL-6, IL-8, and TNF-α [ 166 ]. Yen et al [ 167 ] showed that, in a rat model, tidal volume was associated with the expression of complement/coagulation cascade proteins, and low end-expiratory lung volumes were associated with expression of mitochondrial respiratory chain protein. They concluded that that tidal stretch and lung collapse can activate different pathways.…”
Section: Omics In Ards Researchmentioning
confidence: 99%
“…Peptide fractions were analysed using 90 min nano ow HPLC gradient and a Top15 DDA-MS method as previously described (9). Individual peptide samples (~1 mg peptide) were analysed by DIA-MS using 26 × 25 amu sequential MS2 scans over the range of 397.5-1027.5 m/z, with 1 amu overlap between windows between MS1 spectra (390 -1240 m/z) acquired at 120k resolution.…”
Section: Proteomic Analysismentioning
confidence: 99%
“…As described previously [ 5 ], asthma and allergic conditions were defined by questionnaire and skin-prick tests respectively, while exposure to annual outdoor NO 2 concentrations was estimated using a validated satellite-based land-use regression model approach [ 6 ]. We measured serum 25-hydroxyvitamin D 3 (25(OH)D 3 ) levels using liquid chromatography–tandem mass spectrometry (LC-MS/MS) and analysed the proteomic profile using Orbitrap LC-MS/MS [ 7 ]. We categorised the participants into low or high NO 2 exposure groups using a threshold of 5.1 ppb based on the mean annual NO 2 exposure of the TAHS cohort (5.1±2.6 ppb, n=1367) [ 5 ] and we defined vitamin D deficiency as a 25(OH)D 3 level <50 nmol·L -1 [ 8 ].…”
mentioning
confidence: 99%